Software quality improvement model for small organizations - Mansour, Nashat (2003)
Small software organizations are not capable of bearing the cost of establishing classical software process improvement programs. In this work, we propose a new software quality improvement model for small organizations (SQIMSO), based on three major issues. Firstly, every improvement program should be wide enough to include the major trends. Secondly, any process quality model should answer the question “How to do things?” Thirdly any suggested quality model should be practical enough to be implemented by small software organizations. SQIMSO also draws upon international quality standards, models, and experiences.